Cytotoxicity Induced by Tetracyclines via Protein Photooxidation. (24th March 2015) - Fuoco, Domenico
Abstract : Background . Bacterial ribosomes have been considered the principal targets of tetracyclines. Recently, new clinical data has shown how other biomacromolecules are involved in the cellular damage of bacteria. Researchers are now reconsidering the pharmacological classification of tetracyclines, not only based on their semisynthetic or synthetic generations but also following the new mechanisms of action that are progressively being discovered. Materials and Methods . The toxicity properties of seven tetracycline derivatives (tetracycline, oxytetracycline, demeclocycline, chlortetracycline, doxycycline, minocycline, and meclocycline) were investigated in vitro using a cell line of human keratinocytes. Cells were irradiated in the presence of tetracyclines for different durations and at three different intensities of light. The investigation of protein oxidation was set up using model proteins to quantify the formation of carbonyl groups. Results . After incubation and irradiation with UV light, the viability of keratinocytes was assessed with half the maximal inhibitory concentration for doxycycline, demeclocycline, chlortetracycline, and tetracycline. No phototoxicity was observed for oxytetracycline, meclocycline, and minocycline. Conclusions . This study provides evidence that tetracycline's derivatives show different photobehaviour according to their chemical properties due to different reactive groups on the same molecular skeleton.